A semi-automated robotic system for percutaneous interventions - Siegfarth, Marius; Lutz, Raffael; Iseke, Nils-Christian; Moviglia, Javier; Sadi, Fabian; Stallkamp, Jan (International journal of computer assisted radiology and surgery, 2023)
A robotic assistive device is developed for needle-based percutaneous interventions. The aim is a hybrid system using both manual and actuated robotic operation in order to obtain a device that has a large workspace but can still fit in the gantry opening of a CT scanner. This will enable physicians to perform precise and time-efficient CT-guided percutaneous interventions. The concept of the mechanics and software of the device is presented in this work.